Establishment of Average Body Measurements and Development of Block Patterns for Adolescent Boys in Nigeria - Anne, Igbo Chinyere (Nurture, 2007)
The purpose of this study was to establish average body measurements and develop block patterns for shirts and trousers for adolescent Boys in Nigeria. The survey research design and quasi-experimental design were used for the study. A sample of 399 adolescent boys were measured and arranged in three categories of small, medium and large. The measurements were standardized to obtain average body measurement for the boys. Data obtained were used to draft block patterns for the three categories of adolescents. The patterns were, front shirt, back shirt, sleeve, trouser front and back. Three shirts and three pair of trousers were constructed on calico from the pattern pieces drafted. The shirts and trousers were fitted on three adolescent boys, small, medium and large who also acted as models. Judges and the models assessed the shirts and trousers for fit and comfort using a five point scale. Mean was used for data analysis. A mean score of less than or more than 3.00 showed that the garment was either bigger or smaller than the size considered comfortable, and needs to be altered, while a mean of 3 indicated that the patterns fitted and were comfortable. Minor alterations were made on certain areas of the patterns and final patterns traced out. Recommendations were made based on the established average body measurements and the block patterns produced.